Effect of Skin Barrier Damage on Absorption and Action of Cosmeceuticals - Suraj Sen; Anit Jha; Praveen Yadav; Ujala; Anushka Maurya (Recent Trends in Cosmetics, 2026)
The skin acts as a primary defensive barrier protecting the human body against environmental aggressors, microbial invasion, and chemical exposure. The integrity of the skin barrier, particularly the stratum corneum, plays a crucial role in regulating the permeation of substances applied topically. Cosmeceuticals, a hybrid category between cosmetics and pharmaceuticals, are designed to deliver biologically active ingredients into the skin to exert therapeutic or beneficial effects. However, the condition of the skin barrier significantly influences their absorption, efficacy, and safety. Skin barrier damage may arise due to intrinsic factors such as aging and genetic predisposition, as well as extrinsic factors including UV radiation, pollution, harsh chemicals, and excessive use of skincare products. Disruption of the barrier leads to increased transepidermal water loss (TEWL), altered lipid composition, and compromised structural organization, which in turn affects percutaneous absorption pathways. While mild barrier impairment may enhance penetration of active ingredients, severe damage can lead to uncontrolled absorption, irritation, inflammation, and systemic exposure risks. This review comprehensively explores the relationship between skin barrier damage and the absorption dynamics of cosmeceuticals. It discusses the structural and functional aspects of the skin barrier, mechanisms of its disruption, and fundamental principles of transdermal drug delivery. Additionally, the article highlights how formulation strategies can be optimized for compromised skin conditions, ensuring both efficacy and safety. Current research trends, clinical implications, and regulatory considerations are also addressed to provide a holistic understanding of this critical area.
Keywords: Barrier Dysfunction; Cosmeceuticals; Dermatopharmaceutics; Percutaneous Absorption; Skin Barrier; Skin Permeation; Trans epidermal Water Loss; drug delivery; stratum corneum; topical formulation